Four species of Brazilian poison frogs related to Epipedobates pictus (Dendrobatidae): taxonomy and natural history observations - Haddad, C. F B; Martins, M. (My University, 1994)
Presents morphological and natural history data on Epipedobates pictus and three additional taxa currently regarded as synonyms of the former: Epipedobates braccatus, E. flavopictus and E. hahneli. Morphological data on tadpoles and adults, in addition to distribution patterns and vocalizations, indicate that the four taxa represent distinct species. -from Authors
Keywords: poison frog; taxonomy; Brazil; Dendrobatidae; Epipedobates braccatus; Epipedobates flavopictus; Epipedobates hahneli; Epipedobates pictus